Clinical Handbook of Transcultural Infant Mental Health - Lecannelier-Acevedo, F (Springer International Publishing, 2019)
This handbook provides a review of relevant topics concerning the interface between culture and mental health, with a particular focus on child-rearing practices and transcultural issues in the perinatal period, infancy, and early childhood. It discusses how to work with infants and families from diverse backgrounds and addresses the most common issues that medical and mental health experts may encounter when working with individuals from other cultures. Chapters examine the considerable range of child-rearing strategies and how families from various cultural groups approach issues such as infant sleep, feeding practices, and care during pregnancy. In addition, chapters address conditions that are seen mostly within a particular sociocultural context and are "culture bound" syndromes or states. The handbook concludes with the editors recommendations for future research directions. Topics featured in this handbook include: Prejudice, discrimination, and stereotyping within the clinical field. Cultural responses to infant crying and irritability. Cultural issues in response to chronic conditions and malformations in infancy. The healthy immigrant effect. The use of folk and traditionally therapeutic remedies. The Clinical Handbook of Transcultural Infant Mental Health is an essential resource for researchers, clinicians and related professionals, and graduate students in infancy and early child development, child and school psychology, pediatrics, social work, obstetrics, and nursing. © Springer Nature Switzerland AG 2019. All rights reserved.